PENGARUH SARANA DNA PRASARANA AKADEMIK TERHADAP MINAT BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2023 - Sabrina Erisa Aulia Sihotang; Khairunnisa Umi Almas; Siti Mardiah; Dwi Atika Zahara; Eki Monalisa Surbakti; Yohanna Sitanggang; Mica Siar Meiriza (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Abstract Learning infrastructure and facilities are direct and indirect needs to improve the quality of learning and students' interest in learning. The reason the researcher conducted this research was that the researcher wanted to understand the extent of the impact of facilities and infrastructure on students' interest in learning in the 2023 Economic Education Stambuk; therefore, the researcher chose the research title "The Impact of Academic Facilities and Infrastructure on Student Interest in Learning" in the 2023 Economic Education Stambuk, carried out using quantitative prescriptive strategies. The specimen collection method used in this research is a sampling model, namely distributing a questionnaire via Google Form. This approach was chosen because it provides comprehensive information regarding the relationships between the variables studied. The results of this research are presented in the form of tables, charts, and/or graphs. In this component, the results and discussion will explore data analysis in order to prove the relationship between academic facilities and infrastructure variables and study interest variables, provide logical explanations for the findings obtained, and provide references related to analyses that have been carried out or carried out partially, as well as simple linear regression obtained by several scholars. Facilities and infrastructure have an important influence on interest in learning. The results of the t test prove that the calculated t value with the t table is (4.922 > 2.048), and the significance is 0.000 < 0.05. The results of the analysis of the coefficient of determination show that the level of influence of academic facilities and infrastructure on interest in learning is 46.4%. This means that interest in learning can be determined by X1, namely facilities and infrastructure.